Study on Defect Detecting and Locating Method of Tubular Cylindrical Conductor - Yinchuan Wu; Baolong Guo; Jiatian Zhang; Zhengguo Yan (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
This paper is to present a defect detecting and locating method of tubular cylindrical conductor based on alternating current impedance measurement theory. A defect estimation  can be made through the impedance measurement of some distance on the inner and the outer surfaces of the tubular cylindrical conductor. A defect in the thickness direction can be located by the skin effect influence on impedance and the frequency change in exciting current. The results show that: this method can effectively identify and locate a defect, and therefore should be promoted in the defect detecting of metal materials in other shapes. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2676